Get me through the next five minutes : odes to being alive - Parker, James, 1968- (W.W. Norton & Company, 2024)
"Our politics are broken; our world is melting; the next catastrophe looms. Enter James Parker, who for years now has been writing odes of appreciation on subjects from the seemingly minor ("Ode to Naps") to the unexpected ("Ode to Giving People Money") to the seemingly minor, unexpected, and hyperspecific ("Ode to Running in Movies"). Finally collecting Parker's beloved and much-lauded odes in one place, this volume demonstrates the profound power of the form. Each ode is an exercise in gratitude. Each celebrates the permanent susceptibility of everyday humdrum life to dazzling saturations of divine light: the squirrel in the street, the crying baby, the misplaced cup of tea. Parker's odes are songs of praise, but with a decent amount of complaining in there, too: a human ratio of moans. Varied in length but unified in tone, mostly in prose, sometimes toppling into verse, the odes range across music, movies, literature, psychology, and beyond, all through the lens of Parker's personal history. Gathered together, they form an accidental how-to guide to honoring your own experience-and to finding your own odes"--